2010
DOI: 10.5539/jas.v2n2p147
|View full text |Cite
|
Sign up to set email alerts
|

Screw Conveyors Power and Throughput Analysis during Horizontal Handling of Paddy Grains

Abstract: The tests reported in this research were conducted to determine the effects of those parameters believed to have the greatest influence upon horizontal screw conveyors throughput capacity and power requirement when handling paddy grains. Two screw conveyors with diameters of 20 and 25 cm were evaluated at four screw clearances (6, 9, 12 and 15 mm) and five screw rotational speeds (200, 300, 400,500 and 600 rpm). The results revealed that for both the conveyors tested, with increasing the screw rotational speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…(10), the most interesting cases of torsional oscillations from the theoretical and practical point of view are cases: а. 4 2 0 0…”
Section: Formulation Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…(10), the most interesting cases of torsional oscillations from the theoretical and practical point of view are cases: а. 4 2 0 0…”
Section: Formulation Of the Problemmentioning
confidence: 99%
“…In works [4][5][6][7][8] it was used the method of discrete elements for the analysis of the productivity of screw conveyer including visualization of motion of particles, the angular and axial speed of particles and on the whole twisty moment and total force. It is built the model by application of its periodic border for one step of screw and the particle of friable material, it is shown the dependence of the productivity ofscrew conveyer on operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Transport of settled solids is conducted using the screw conveyor. Whereas it can be powered through human endeavour, this study assumes the screw conveyor, which has a conservative specific power requirement of 0.056 Wh/kg settledsolids [31] , [32] , is electrically driven by power generated in the Stirling engine. To accurately account for the composition of the settled solids, these are modelled as a nonconventional component with proximate and ultimate analysis provided in Table 1 , and heating value determined from its composition using Dulong’s formula.…”
Section: Model Developmentmentioning
confidence: 99%
“…The screws used for free flowing bulk solids, giving better throughput control and providing clean environmentally system for handling grains owing to their simple form, high performance, less price and maintenance. Also, Zareiforoush et al (2010) They designed a special screw conveyor for rice specie called Hashemi and reported that the specific power requirements increased of the conveying screws by increasing the screw clearance and screw velocity. Also, the actual volumetric capacity increased up to a maximum value by increasing rotational conveyor screw conveyor rotational speed.…”
Section: Introductionmentioning
confidence: 99%